Interaction Between Educational Institution and Employers’ Organizations in Cultural Sphere: Study Experience - A. V. Shtoler; N. N. Shtoler; K. L. Yaprintseva (Высшее образование в России)
The article presents the results of the study held in the Chelyabinbsk State Institute of Culture in 2021. The study aimed at the evaluation by employers’ organizations of the university graduates’ preparation level, requirements of professional sphere to the competencies of culture workers, and determination of forms and directions of employers’ participation in educational process. The study showed comparatively high evaluation of educational system results (training of a graduate), the developed personal characteristics, universal and professional competencies of a culture worker. The authors have also revealed a dominant orientation at short-term, local (according to scales, intensity and the tasks realized) directions and forms of interaction between the university and regional sphere of culture. The choice of tools for such interactions indicates a lack of long-term aims, strategic character and focus on the solution of the personnel potential reproduction tasks and integration of cultural institutions into educational process, organization of joint scientific-research, artistic and creative, sociocultural projects. Meanwhile, interaction potential of cultural activity and professional education spheres becomes a factor of protecting and development of regional system of culture, sociocultural transformation of the corresponding territories.